2012
DOI: 10.1105/tpc.112.097741
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Starvation Signals and Hormone Crosstalk in Regulating Nutrient Mobilization upon Germination in Cereals

Abstract: Germination is a unique developmental transition from metabolically quiescent seed to actively growing seedling that requires an ensemble of hydrolases for coordinated nutrient mobilization to support heterotrophic growth until autotrophic photosynthesis is established. This study reveals two crucial transcription factors, MYBS1 and MYBGA, present in rice (Oryza sativa) and barley (Hordeum vulgare), that function to integrate diverse nutrient starvation and gibberellin (GA) signaling pathways during germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 63 publications
0
65
0
Order By: Relevance
“…Earlier publications proposed that GA 3 -induced hydrolysis of starch reserves is a post-germinative event not associated with GA 3 -induced breaking of dormancy (Simpson and Naylor 1962;Foley et al 1993). According to the present views, starch is a major carbon source for generating the energy required for seed germination and early seedling growth (Hong et al 2012;Yan et al 2014;Shaik et al 2014). Moreover, a-amylase was considered as a candidate biomarker for rice seed germination (He and Yang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier publications proposed that GA 3 -induced hydrolysis of starch reserves is a post-germinative event not associated with GA 3 -induced breaking of dormancy (Simpson and Naylor 1962;Foley et al 1993). According to the present views, starch is a major carbon source for generating the energy required for seed germination and early seedling growth (Hong et al 2012;Yan et al 2014;Shaik et al 2014). Moreover, a-amylase was considered as a candidate biomarker for rice seed germination (He and Yang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings in sucrose-specific stabilization of the DELLA repressors support an antagonistic relationship between sucrose and gibberellin signaling and the opposite roles in anthocyanin biosynthesis uncoupled from HXK1 signaling (Loreti et al, 2008; Li et al, 2013). Comprehensive studies in the rice and barley aleurones indicate that gibberellin and SNRK1A (SNF1-RELATED PROTEIN KINASE1A) antagonize sugar repression and promoting the nuclear translocation and activity of MYBS1 and MYBGA, which is also enhanced by nitrogen and phosphate deficiency but mostly uncoupled from the HXK1 glucose sensor functions (Lu et al, 2007; Hong et al, 2012). …”
Section: Direct Glucose Sensing and Signaling Via Hxk1mentioning
confidence: 99%
“…Differential cellular localization appears to be a key factor in this regulatory process. It has been demonstrated previously that the crucial GA regulator MYBGA facilitates the function and nuclear import of MYBS1 (Chen et al, 2006;Hong et al, 2012). Here, we further showed that sugar and nutrient demands, which are important signals from the sink tissue (germinating embryo and seedling), trigger the conuclear localization of two starvation signaling factors Barley aleurone was transfected with Ubi:SnRK1A-GFP and incubated in +S or -S medium with ABA (+ABA) or without ABA (2ABA) for 48 h. Percentages indicate the number of cells with GFP distribution in the indicated category divided by the total number of cells examined.…”
Section: Differential Cellular Localization Of Key Factors Regulates mentioning
confidence: 99%
“…GA also activates a-amylase gene promoters through the GA response complex, in which the adjacent GA response element and the TA/Amy box are key elements and act synergistically (Rogers et al, 1994;Gubler et al, 1999;Gómez-Cadenas et al, 2001). MYBGA (also called GAMYB) is a GA-inducible R2R3 MYB that binds to the GA response element and activates promoters of a-amylases and other hydrolases in cereal aleurone cells in response to GA (Gubler et al, 1995(Gubler et al, , 1999Hong et al, 2012). Our recent study revealed that the nuclear import of MYBS1 is repressed by sugars, and GA antagonizes sugar repression by enhancing the conuclear transport of MYBGA and MYBS1 and formation of a stable bipartite MYB-DNA complex to activate a-amylase gene promoters .…”
Section: Introductionmentioning
confidence: 99%